Investigação dos livros didáticos com foco na História da Matemática - Souza, Maitê Duarte Sedenho de (Universidade Federal de São Carlos, 2022)
We have observed that the History of Mathematics often goes unnoticed by students during problem solving or the study of mathematical content. In this work we seek to analyze how is the approach of the History of Mathematics in some textbooks, from the 1950 to the present, focusing on its historical approach and the connection in the approach of mathematical exercises. In addition, we analyzed the teaching material from three schools, one state, one municipal and one from the private network, in order to identify the approach to the History of Mathematics in the exercises and in the theoretical part of the content. Then, we elaborate and apply an activity suggestion that relates the History of Mathematics with Egyptian numbers, allowing the student to visualize the history together with the resolution of problems and provide the student's role in the creation of mathematical problems involving Egypt
Investigation of textbooks focusing on the History of Mathematics
Keywords: História; Matemática; Números; Egípcios; History; Mathematics; Egyptian; CIENCIAS HUMANAS::HISTORIA::HISTORIA DAS CIENCIAS